Peculiarities of Multivariate Analysis Based Methods for Detection and Evaluation of ECG T-wave Alternans - Krakauskaite, S.; Simoliuniene, R.; Petrolis, R.; Krisciukaitis, A. (Elektronika ir Elektrotechnika, 2013)
Two multivariate analysis methods based on Principal Component Analysis and Periodic Component Analysis designed for detection and evaluation of ECG T-wave alternans were tested on synthetic and clinical recordings in the aim to reveal their diagnostic features. Advanced data pre-processing including normalization of S-T,T segment duration by means of bicubic interpolation was used to increase methods reliability. Non-visible variations in shape of S-T,T segment were revealed by means of the methods in the recordings registered in severe cardiac situations. Results lead to the idea, that analysis of T-wave alternans could be used not only for prevention of critical cardiac situations, but give valuable additional diagnostic information about status of cardiologic patients during ordinary examination. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5655